La selva que camina - Mediador itinerante para la apropiación del patrimonio presente en el patrimonio de Cerro Pinturas – Guaviare (2023)
The following work compiles an investigation about the heritage present in the Cave Manifestations of Cerro Pinturas - Guaviare and how through this, industrial design can transform this information into objects and experiences interesting enough to link the new generations. In other words, how industrial design applies its knowledge and techniques to generate new types of approaches to heritage and historical themes through interactions.